Wearable Fixation Device for a Magnetically Controllable Therapeutic Agent Carrier: Application to Cartilage Repair - Kyungmin Lee; Gwangjun Go; Ami Yoo; Byungjeon Kang; Eunpyo Choi; Jong-Oh Park; Chang-Sei Kim (MDPI AG, 2020)
Recently, significant research efforts have been devoted toward the development of magnetically controllable drug delivery systems, however, drug fixation after targeting remains a challenge hindering long-term therapeutic efficacy. To overcome this issue, we present a wearable therapeutic fixation device for fixing magnetically controllable therapeutic agent carriers (MCTACs) at defect sites and its application to cartilage repair using stem cell therapeutics. The developed device comprises an array of permanent magnets based on the Halbach array principle and a wearable band capable of wrapping the target body. The design of the permanent magnet array, in terms of the number of magnets and array configuration, was determined through univariate search optimization and 3D simulation. The device was fabricated for a given rat model and yielded a strong magnetic flux density (exceeding 40 mT) in the region of interest that was capable of fixing the MCTAC at the desired defect site. Through in-vitro and in-vivo experiments, we successfully demonstrated that MCTACs, both a stem cell spheroid and a micro-scaffold for cartilage repair, could be immobilized at defect sites. This research is expected to advance precise drug delivery technology based on MCTACs, enabling subject-specific routine life therapeutics. Further studies involving the proposed wearable fixation device will be conducted considering prognostics under actual clinical settings.